2022
DOI: 10.55519/jamc-03-9596
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Scaphoid Megalourethra: Revisiting a Rare Anomaly

Abstract: Megalourethra is an infrequent malformation of the anterior urethra that is caused by the lack of corpus sponigosum and in severe cases is accompanied by the lack of corpora cavernosa as well. We report a five-year-old boy presented to us with scaphoid variety of megalourethra having complaints of ballooning of urethra during voiding. He was investigated with urethrogram and cystoscopy and subsequently repaired with Nesbitt Longitudinal Reduction Urethroplasty. He had smooth recovery postoperatively with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Nine studies 3,5,10,1319 ( n = 47,985 patients) were included in the final analysis. There were 7 RCTs ( n = 928) 3,10,1317 and 2 observational studies ( n = 47,007) 5,18 included in the analysis. One observational study was removed during analysis because it only reported raw data and we analyzed adjusted odds ratios with standard errors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies 3,5,10,1319 ( n = 47,985 patients) were included in the final analysis. There were 7 RCTs ( n = 928) 3,10,1317 and 2 observational studies ( n = 47,007) 5,18 included in the analysis. One observational study was removed during analysis because it only reported raw data and we analyzed adjusted odds ratios with standard errors.…”
Section: Resultsmentioning
confidence: 99%
“…13 One study had uncertain risk of bias due to uncertain randomization process and how missing outcome data was addressed. 10 Supplementary Figure 3 summarizes the Risk of Bias Assessment tool for Non-randomized Studies (RoBANS) for all included observational studies. One of 3 studies had high risk of bias for selection of participants since it was a before/after study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations